Penegakan Hukum Terhadap Pelaksanaan Penyelidikan dan Penyidikan Terhadap Tindak Pidana Penyalahgunaan Psikotropika - Ester Afrilin Watuseke; Margo Hadi Pura (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study is to better understand the process of investigating criminal acts of psychotropic abuse, the role of law enforcement and the community in these investigations, the effectiveness of criminal sanctions outlined in Law Number 5 of 1997 against these crimes, and the best way to prevent and reduce these crimes. In order to draw the following conclusions, a normative juridical research approach was used for this investigation: 1. The efforts of Indonesian law enforcement in combating the abuse and illicit traffic of psychotropics are highly praised. The Indonesian government approved the Vienna Convention on Psychotropics in 1988, which provided the legal basis for Law Number 5 of 1997. Law enforcement agencies can greatly benefit from the special procedural law set forth in Law Number 5 of 1997 when conducting investigations into cases involving psychotropic crimes. 2. The death penalty is an option for those who commit heinous narcotics crimes, as stipulated in the Criminal Code and Law Number 5 of 1997. The Constitutional Court ruled that executing drug dealers does not violate their human rights, because they have violated the rights of other people, which will have a negative impact on future generations. 3. Legislators and other interested parties have developed and proposed a number of countermeasures to reduce the negative and potentially harmful effects of psychotropic drug abuse. Crime prevention efforts can be divided into two categories: those focused on education and those focused on law enforcement.